Catalogue of the Dryinidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) of Belize, with description of two new species - Schüepp, Christof; Olmi, Massimo (Zootaxa, 2012)
Eighteen species of Dryinidae and one species of Sclerogibbidae are listed from Belize. Two new species of Dryinidae,Anteon dykeae Olmi, sp. nov. and Dryinus schueeppi Olmi, sp. nov., are described from Belize, Corozal District. Keys toNeotropical species of Anteon and Dryinus are modified and include new species. Nine species of Dryinidae and one spe-cies of Sclerogibbidae are newly recorded from Belize. New records of Dryinidae are: four species from Panama, two spe-cies from Paraguay, and one species from Colombia, Mexico, Honduras, Venezuela, Ecuador, Bolivia and French Guiana. The dryinid and sclerogibbid fauna of Belize is still under-sampled and insufficiently known.